Fears and Tears of Transparency and Disclosure: Controversies and Politics of School Profiles in Hong Kong Since 2000. Issue 8 (November 2019) - Tse, Thomas Kwan Choi
One measure of current education reform in Hong Kong is reporting school performance to the public to increase the transparency and accountability of schools, enhance parents' right of access to information, and provide guides for choosing schools. This article examines the controversies and politics involved and shows how the sociopolitical construction of information are connected to crucial questions about how the conflicting values and expectations of different stakeholders are balanced. Advocating public school performance reporting without adequate deliberation could introduce anti-educational and unethical consequences, however unintended. Drawing on the works by Albert Meijer and findings from Hong Kong, this study provides additional empirical evidence and conceptual insights for understanding the complex dynamics of school transparency in the context of public sector accountability. The article concludes with analytical and ethical implications of the Hong Kong experience and recommendations for policy makers, particularly concerning the value judgments on the right to information, freedom of choice, transparency, accountability, freedom of the press, and professionalism.